2019
DOI: 10.1093/fampra/cmz050
|View full text |Cite
|
Sign up to set email alerts
|

Primary care clinicians’ confidence, willingness participation and perceptions of roles in advance care planning discussions with patients: a multi-site survey

Abstract: Background People who engage in advance care planning (ACP) are more likely to receive health care that is concordant with their goals at the end of life. Little discussion of ACP occurs in primary care. Objective The objective of this study was to describe primary care clinicians’ perspectives on having ACP conversations with their patients. Methods We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…Studies investigating ACP in primary care demonstrate an area for improvement. A Canadian study found PCPs were willing and con dent in engaging in ACP discussions, but were not often doing so (38). The same study investigated non-physician HCP willingness, con dence, and engagement in ACP.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Studies investigating ACP in primary care demonstrate an area for improvement. A Canadian study found PCPs were willing and con dent in engaging in ACP discussions, but were not often doing so (38). The same study investigated non-physician HCP willingness, con dence, and engagement in ACP.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Studies investigating ACP in primary care demonstrate an area for improvement. A Canadian study found PCPs were willing and confident in engaging in ACP discussions, but were not often doing so [44]. The same study investigated non-physician HCP willingness, confidence, and engagement in ACP.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Studies investigating ACP in primary care demonstrate an area for improvement. A Canadian study found PCPs were willing and con dent in engaging in ACP discussions, but were not often doing so (46). The same study investigated non-physician HCP willingness, con dence, and engagement in ACP.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%